Scattering layers for Titanium dioxide and Tin dioxide Dye-sensitized solar cells with Pandan leaf as a natural sensitizer - Azwar Hayat (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
Dye-sensitized solar cell with a scattering layer as a light mobility enhancer has been fabricated in this work. The cells were fabricated with two types of semiconductor materials which are Titanium dioxide and Tin dioxide. Natural sensitizer from Pandan leaves was also used as an electron generator combined with liquid electrolyte redox couple Iodide/Tri-Iodide. The photovoltaic performance was measured with four types of semiconductor configurations. It was Titanium dioxide only, Titanium dioxide with scattering layer, Tin dioxide only and Tin dioxide with scattering layer. Pandan dyes have higher photovoltaic performance when fabricated with scattering layers in both semiconductor cells. The scattering layer has boosted the light management inside the photo-anode film and increased the Photo-conversion efficiency. Photo-conversion efficiency parameters such as short-circuit current and open circuit voltage were monitored to improve compared to cells without the scattering layer. Higher electron injection were contributed from the increase of light path on photo-anode film with scattering layers. The incident photon-to-current efficiency graph confirmed that the cells with Titanium dioxide with scattering layer had a higher photon-to-current density than the cells with Tin dioxide only on 300 to 500 nm. The incident photon-to-current efficiency of the device with Tin dioxide with scattering layer was higher than that of the device with Tin dioxide only in the wavelength range of 300 to 700 nm, the dominant effect of the scattering layer was found to affect more in Tin dioxide than Titanium dioxide semiconductors on low to high wavelength of the incident photon-to-current efficiency. It concludes that light management is an important strategy to improve the performance of low-cost and eco-friendly solar cells. This strategy is suitable to enhance the efficiency of DSSC for further low-cost solar cells